Pengaruh Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR) dan BOPO Terhadap Profitabilitas Bank (Studi Kasus pada Bank Umum Swasta Nasional Devisa Go Public di Bursa Efek Indonesia Periode 2014-2016) - Ulfi Aryanti; Saryadi Saryadi (Universitas Diponegoro, 2018)
Public confidence in the banks is influenced by the performance it achieved, thus Bank performance is essential to study. Data from period 2014-2016 shows that the net profitability of BUSN (Foreign Exchange Bank), continued to decline over time. The financial ratios expected to affect the fluctuation in bank profitability are CAR, NPLs, LDR, and BOPO. This study aimed to analyze the effect of CAR, NPLs, LDR, and BOPO on profitability (ROA and ROE) of the Bank. The sample used in the study consisted of 22 private foreign Exchange bank (BUSN) listed on the Indonesia Stock Exchange, period of 2014-2016. The analysis technique used is linear regression analysis and the analysis was done using SPSS program. Based on the analysis result, it is concluded that the variables that affect profitability of the Bank (ROA and ROE) are NPLs and ROA, while the CAR and LDR has no effect on bank profitability (ROA and ROE). From these results, banks are expected to supervise and monitor the use of credit funds so that the NPL remain in the healthy category so as to avoid bad loans. In addition, banks are expected to suppress the amount of operating expenses of BOPO, in order to withstand at the level of efficiency where maximum profit can be attained, hence improve the performance of the bank.